Mechanisms of bone erosion in gout: a quantitative analysis using plain radiography and computed tomography. Issue 8 (15th August 2008) - Dalbeth, N; Clark, B; Gregory, K; Gamble, G; Sheehan, T; Doyle, A; McQueen, F M
Abstract : Objective: The underlying basis of bone erosion in gout remains speculative. The aim of this study was to understand the mechanisms of bone erosion in gout using non-invasive imaging techniques. Methods: Paired plain radiographs and computed tomography (CT) scans of 798 individual hand and wrist joints from 20 patients with gout were analysed. Radiographs were scored for erosion (0–5) using the Sharp/van der Heijde method. CT scans were scored for the presence and diameter of bone erosions and tophi. The presence of intraosseous tophus (tophus visualised within bone) was recorded. The relationships between radiographic erosion, CT erosion and tophus scores were analysed. Results: With increasing radiographic erosion scores, the percentage of joints with intraosseous tophus increased (p<0.001). For those joints with a radiographic erosion score of 4 or 5, 96/98 (98%) had CT evidence of intraosseous tophus. There was a significant relationship between the radiographic erosion scores and intraosseous tophus size (p<0.001). For those joints with CT erosion, 194/237 (81.8%) had visible intraosseous tophus. Of the joints with CT erosions greater than 5 mm, 106/112 (94.6%) had visible intraosseous tophus and all (56/56) erosions greater than 7.5 mm had intraosseous tophus. There was a strong correlation between CT erosion diameter and intraosseous tophus diameter (r  =  0.93, p<0.001). Intraosseous tophi were larger than non-intraosseous tophi, but had similar density and calcification. Conclusion: There is a strong relationship between bone erosion and the presence of intraosseous tophus. These results strongly implicate tophus infiltration into bone as the dominant mechanism for the development of bone erosion and joint damage in gout.